2022
DOI: 10.1097/rlu.0000000000004064
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid PET/MRI in Staging Endometrial Cancer

Abstract: Purpose. Assessment of deep myometrial invasion (MI) and lymphovascular space invasion (LVSI) is of utmost importance in preoperative staging of endometrial cancer (EC). Imaging parameters derived respectively from MRI and PET have shown good predictive value. Aim of the present study is to assess the diagnostic performance of hybrid 18F-FDG PET/MRI in EC staging, with particular focus on MI and LVSI detection.Methods. Prospective monocentric study including 35 patients with biopsy-proven EC undergoing preoper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 46 publications
4
11
0
Order By: Relevance
“…Second, the study design did not routinely include 18 F-FDG PET imaging that could have been associated with positive lesions at least in the small fraction of patients affected by high grade tumors. Third, despite some recent evidence have suggested a possible role for specific texture features in predicting nodal status, 26,28,43,44 this specific and innovative approach for image analysis has not been performed on a CE-CT or PET. Finally, long-term outcomes are still missing and the impact on prognosis of imaging findings is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the study design did not routinely include 18 F-FDG PET imaging that could have been associated with positive lesions at least in the small fraction of patients affected by high grade tumors. Third, despite some recent evidence have suggested a possible role for specific texture features in predicting nodal status, 26,28,43,44 this specific and innovative approach for image analysis has not been performed on a CE-CT or PET. Finally, long-term outcomes are still missing and the impact on prognosis of imaging findings is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…CE-CT and EUS study protocols were previously described 26,27. 68Ga-DOTATOC PET images were acquired as previously described, by using a PET/CT or PET/ magnetic resonance imaging scanner 28…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of PET/MRI in preoperative staging, evaluation of myometrial invasion, cervical interstitial infiltration, lymph node metastasis and distant metastasis, as well as evaluation and prognosis of endometrial cancer has been gradually confirmed. 21 Integrated PET/MRI can not only achieve preoperative staging of endometrial cancer, but also provide metabolic information of tumors and detect early lesions in addition to ensuring precise anatomical localization, while conventional imaging examinations are mainly based on morphological change. 22 Therefore, it provides important reference data for clinicians to determine the extent of surgical resection, guide postoperative radiotherapy and chemotherapy, guide the formulation of radiotherapy scope, and assess the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…18 Ffluoro-deoxyglucose ( 18 F-FDG) positron emission tomography (PET) has a well-established role in the preoperative staging of EC patients, and it is included in the clinical guidelines on EC management [24,25]. Precisely, 18 F-FDG is useful in providing a whole-body assessment of the disease, therefore identifying possible LN involvement and distant metastases [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%